Identifying main interactions in marine predator–prey networks of the Bay of Biscay. (30th July 2019) - Astarloa, Amaia; Louzao, Maite; Boyra, Guillermo; Martinez, Udane; Rubio, Anna; Irigoien, Xabier; Hui, Francis K C; Chust, Guillem
Abstract: Identifying the role that environmental factors and biotic interactions play in species distribution can be essential to better understand and predict how ecosystems will respond to changing environmental conditions. This study aimed at disentangling the assemblage of the pelagic predator–prey community by identifying interspecific associations and their main drivers. For this purpose, we applied the joint species distribution modelling approach, JSDM, to the co-occurrence patterns of both prey and top predator communities obtained from JUVENA surveys during 2013–2016 in the Bay of Biscay. Results showed that the co-occurrence patterns of top predators and prey were driven by a combination of environmental and biotic factors, which highlighted the importance of considering both components to fully understand the community structure. In addition, results also revealed that many biotic interactions, such as schooling in prey (e.g. anchovy–sardine), local enhancement/facilitation in predators (e.g. Cory's shearwater–fin whale), and predation between predator–prey species (e.g. northern gannet–horse mackerel), were led by positive associations, although predator avoidance behaviour was also suggested between negatively associated species (e.g. striped dolphin–blue whiting). The identification of interspecific associations can therefore provide insights on the functioning of predators–prey network and help advance towards an ecosystem-based management.